Risk of urethral stricture recurrence increases over time after urethroplasty. (22nd April 2015) - Han, Justin S; Liu, Joceline; Hofer, Matthias D; Fuchs, Amanda; Chi, Amanda; Stein, Daniel; Dielubanza, Elodi; Ballek, Nathaniel; Gonzalez, Chris M
Abstract Objective To report a single institutional experience with urethroplasty outcomes and success rates at long‐term follow up. Methods A retrospective review was carried out of all urethroplasties performed by a single surgeon from 2000 to 2010. A total of 347 patients underwent urethroplasty during this time period, of which 227 had minimum 1‐year follow‐up data available. Demographic, clinical, pathological and outcome data were reviewed. Recurrence was defined by patient reported urinary symptoms or need for subsequent intervention. Statistical analyses were carried out using SPSS statistical software. Results A total of 26% of all patients had a recurrence at a mean follow up of 62 months (range 13–147 months). The recurrence rate after anastomotic urethroplasty was 18%, as compared with 31% after substitution urethroplasty. Mean time to recurrence was 34 months (range 5–87). On univariate analysis, use of abdominal skin graft, history of prior urethroplasty, lichen sclerosus and length of follow up were statistically significant predictors of recurrence. On multivariate analysis, only history of prior urethroplasty and length of follow‐up time exceeding 48 months were statistically significant predictors of recurrence. Conclusions Urethroplasty for urethral stricture is the most durable treatment modality, regardless of surgical approach. However, there is an ongoing risk of recurrence with the passage of time. Patients should be counseled appropriately on the potential for late recurrence of stricture disease after urethroplasty.